Assessment of treatment options for patients with hepatitis C virus recombinant form 2k/1b. Issue 2 (11th December 2020) - Zakalashvili, Mamuka; Zarkua, Jaba; Gish, Robert G.; Zhamutashvili, Maia; Sartania, Vakhtang; Weizenegger, Michael; Bartel, Jan; Raabe, Monika; Gvinjilia, Lia; Metreveli, Sophia; Barnova, Maka; Abramishvili, Nikoloz; et al.
Abstract : Aim: Hepatitis C virus (HCV) intergenotype recombinant form (RF) 2k/1b has been actively circulating in HCV‐infected patients, and the prevalence of this RF virus in the Republic of Georgia is one of the highest reported worldwide. The aim of this study was to define the optimal treatment regimen for patients with RF_2k/1b. Methods: We analyzed the data of 2735 patients who started treatment at the Medical Center Mrcheveli within Georgia's hepatitis C elimination program from May 2015 through December 2019. The patients were treated with sofosbuvir (SOF)‐based regimens. For identification of RF_2k/1b variants, refinement of standard (INNO‐LiPA) genotyping results for all patient samples assigned the unspecific HCV genotypes (GT) 2a/2c was carried out by sequencing of core and non‐structural protein 5B genes. Results: Overall, 444 patients, representing 66% of GT2 and 16% of the total samples, were RF_2k/1b. Treatment of patients with RF_2k/1b with SOF/ledipasvir and SOF/velpatasvir was highly effective and viral cure rates did not differ among genotypes treated with the same regimen: RF_2k/1b, 99% (343/346); GT1, 99% (876/885); GT2, 96% (156/162); and GT3, 99% (545/552). A separate comparison analysis of sustained virologic response rate, treated with SOF plus ribavirin, showed significantly higher sustained virologic response (96%) in patients with confirmed GT2 (by sequencing) compared to unspecified GT2 (by INNO‐LiPA) (79%) ( P < 0.05). Conclusion: Sofosbuvir‐based regimens are highly effective for treatment of RF 2k/1b patients, and with availability of new pan‐genotypic direct‐acting antivirals, genotyping to identify RF 2k/1b patients might not be necessary.